2015
DOI: 10.1016/j.actamat.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of low-lying optical phonons in lattice thermal conductance of rare-earth pyrochlores: A first-principle study

Abstract: Rare-earth pyrochlores, commonly exhibiting anomalously low lattice thermal conductivities, are considered as promising topcoat materials for thermal barrier coatings. However the structural origin underlying their low thermal conductivities remain unclear. In the present study, we investigated the phonon properties of two groups of RE pyrochlores, Ln2Zr2O7 (Ln = La, Nd, Sm, Gd) and Gd2T2O7 (T = Zr, Hf, Sn, Pb) employing density functional theory and quasi harmonic approximation.Through the relaxation time app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 71 publications
(109 reference statements)
5
45
0
Order By: Relevance
“…The elastic constants reported by Lan et al . employing GGA method are generally smaller than our LDA results, while they also found that the results of Gd 2 Zr 2 O 7 and Sm 2 Zr 2 O 7 are very similar to each other 36 . We find that the mechanical stability criteria, i.e., (C 11 -C 12 ) > 0, C 44  > 0, and (C 11  + 2C 12 ) > 0 1 , are satisfied for all compounds, indicating that Sm-substituted Gd 2 Zr 2 O 7 compounds are mechanically stable.…”
Section: Resultssupporting
confidence: 60%
“…The elastic constants reported by Lan et al . employing GGA method are generally smaller than our LDA results, while they also found that the results of Gd 2 Zr 2 O 7 and Sm 2 Zr 2 O 7 are very similar to each other 36 . We find that the mechanical stability criteria, i.e., (C 11 -C 12 ) > 0, C 44  > 0, and (C 11  + 2C 12 ) > 0 1 , are satisfied for all compounds, indicating that Sm-substituted Gd 2 Zr 2 O 7 compounds are mechanically stable.…”
Section: Resultssupporting
confidence: 60%
“…However, according to the phonon calculations presented in Ref. [22], pyrochlores in which the B-site cation is a member of group IV, such as Sn, Ge, or Pb, have significantly different phonon frequencies. In comparison with the partial phonon densities of states calculated for a subset of zirconate and hafnate pyrochlores [22], we find that the phonon band structures of (3+,4+) pyrochlores have essentially identical features, with adjustments that can be classified generally in two ways, as illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[22], pyrochlores in which the B-site cation is a member of group IV, such as Sn, Ge, or Pb, have significantly different phonon frequencies. In comparison with the partial phonon densities of states calculated for a subset of zirconate and hafnate pyrochlores [22], we find that the phonon band structures of (3+,4+) pyrochlores have essentially identical features, with adjustments that can be classified generally in two ways, as illustrated in Fig. 11: First, the larger ionic radii of both A and B ions lead to an expansion of the unit cell, which reduces the frequencies of phonon vibrations across the entire phonon spectrum, especially of the phonon modes dominated by the light oxygen ions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations